2006
DOI: 10.1061/(asce)0733-9372(2006)132:9(1061)
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting the Benefits of Primary Clarification versus Prefermentation in Activated Sludge Biological Nutrient Removal Systems

Abstract: The potential benefits prefermentation can provide to biological nutrient removal are measured and compared to the costs of excess oxygen consumption and sludge production incurred by an activated sludge system that utilizes prefermentation, instead of primary clarification. Prefermentation was found to produce superior performance in regards to enhanced biological phosphorus removal. A lower soluble orthophosphorus effluent value ͓3.2 mg/ L for the prefermented activated sludge ͑PAS͒ train versus 4.6 mg/ L fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…COD (RBCOD) and in particular the VFA fraction of the RBCOD has been established in several studies (Brinch et al 1994;Gonç alves et al 1994;Pitman 1999). Prefermentation has proved to be a good option for the production of VFA by using wastewater's own internal carbon sources, but recent studies have reported that prefermentation significantly increases the oxygen requirements (McCue et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…COD (RBCOD) and in particular the VFA fraction of the RBCOD has been established in several studies (Brinch et al 1994;Gonç alves et al 1994;Pitman 1999). Prefermentation has proved to be a good option for the production of VFA by using wastewater's own internal carbon sources, but recent studies have reported that prefermentation significantly increases the oxygen requirements (McCue et al 2006).…”
Section: Introductionmentioning
confidence: 99%